ANALISIS FONOLOGI DALAM PEMEROLEHAN BAHASA PADA RAYYANZA MALIK AHMAD USIA 1 TAHUN - Juliana, Agnessya; Nasution, Firmansyah; Novia Purba, Juli; Mukhlis, Muhammad (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to conduct a phonological analysis on the language acquisition of Rayyanza Malik Ahmad, a 1 year old child. Phonology is a branch of linguistics that studies sound systems in a language. Language acquisition is a process in which a child learns and develops language skills. This research focuses on observing Rayyanza's phonological development, including the sounds he produces, the improvement of his speaking skills, as well as the influence of the environment and social interactions in his language acquisition. The research method used is a case study with a qualitative approach. Data was collected through direct observation of Rayyanza in various daily communicative contexts, such as when interacting with parents, family and the surrounding environment. The phonological analysis was carried out by paying attention to the sounds produced by Rayyanza, such as vowels, consonants, and the pattern of pronunciation of the initial words that were made. The results showed that at the age of 1 year, Rayyanza had shown an early ability in language acquisition. He is able to make several vowel sounds such as /a/, /i/, /u/, as well as several consonants such as /m/, /p/, /n/. However, it should be noted that Rayyanza's sound production is still in its infancy, and there are variations in sound pronunciation that do exist. Environmental factors also play an important role in the acquisition of the Rayyanza language. Interaction with parents, family, and the surrounding environment provides the linguistic stimulus needed for language development. Rayyanza gradually adopted and imitated the sounds she heard around her, as well as trying to say simple words.